Digital Marketing Trends and Consumer Engagement : Insights from Global E-Marketing Campaigns - Michael Carter; Sarah Hayes; Emily Brooks (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study analyzes emerging trends in digital marketing and their impact on consumer engagement. By examining global e-marketing campaigns, the research identifies key strategies such as influencer partnerships, content marketing, and interactive advertisements. Findings reveal that personalization, data-driven insights, and real-time engagement are critical for building lasting customer relationships in the digital age. Despite the potential for higher engagement, challenges like privacy concerns and platform saturation must be addressed to optimize marketing effectiveness.